Dampak Konsumerisme Menonton Konser Musik Indonesia Di Kalangan Anak Muda - Bunga Farah Fauziah; Rizki Setiawan (Peneliti.net, 2023)
Culture is a habitual way of life that continues to develop from time to time, while music is a form of art that will never be separated from human life. In the culture of watching music concerts, it has also developed from time to time. This is due to information and communication technology factors. However, there are many variables that have a negative and positive impact on watching music concerts, especially among young people. Thus, the aim of the researcher is to find out what are the negative and positive impacts of watching Indonesian music concerts among young people. And the results of this study are that there are negative impacts including purchases without a clear purpose, waste, shifting Indonesian cultural values and so on. The positive impact is reducing stress, increasing feelings of well-being and increasing connections from the community.